TANGGUNGJAWAB HUKUM PILOT DALAM KECELAKAAN PENERBANGAN DI INDONESIA - Suhariadi, Saddam Farrell Raid (Universitas 17 Agustus 1945 Samarinda, 2025)
ABSTRACT. In the context of Indonesian law, the aspect of pilot responsibility is also regulated by the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 77 of 2011 which regulates compensation for passengers in aviation accidents. Article 308 of Law Number 1 of 2009 concerning Aviation affirms the responsibility of flight operators for the safety, security, and comfort of passengers, which is also indirectly related to the responsibility of pilots. This research is about the Legal Provisions in Indonesia that regulate the responsibility of Pilots in Aviation Accidents and the obstacles faced in the implementation of regulations regarding the legal responsibility of pilots in accidents. Using normative research, in this case a process to find legal rules, legal principles, and legal doctrines to answer the legal problems raised, using a legislative approach. The results of the research and discussion that the legal provisions in Indonesia that regulate the responsibility of pilots in aviation accidents are quite comprehensive, involving various laws and regulations, ranging from the Aviation Law, CASR, Criminal Code, to ministerial regulations. Then the implementation of regulations regarding the legal responsibility of pilots in aviation accidents faces various obstacles, ranging from the complexity of investigations, limited resources, public pressure, conflicts of interest, protection of pilots, to lack of legal awareness and education. Keywords: Responsibilities, Pilots, Aviation.